INFLUENCE OF THE POLIGONUM AVIOULARE EXTRACT ON THE FUNCTIONAL STATE OF KIDNEYS OF WHITE RATS INTOXICATED BY BICHLORIDE OF MERCURY - A. G. Mondodoev (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents data on the influence of the Poligonum aviculare L. dry extract on the functional state of kidneys of white rats at the nephropathy by bichloride of mercury. It was determined that the extract had. nephroprotective and antioxidative activity.